2019
DOI: 10.1590/1679-78255708
|View full text |Cite
|
Sign up to set email alerts
|

An Anchorage System for Enhanced Bond Behavior between Carbon Fiber Reinforced Polymer Sheets and Cracked Concrete

Abstract: The contribution of CFRP wraps, as an anchorage system, to enhancing bond behavior between CFRP sheet and cracked concrete, was investigated. Thirty six concrete blocks (150 x 150 x 200 mm) were cast with 3ϕ12 mm steel bars embedded laterally at different spacing along the 200-mm-dimension. Half of the moist-cured blocks were subjected to a cyclic treatment in 3% chloride solution until reinforced sides cracked at an average global crack size 0.54 mm; the remaining ones were immersed in a lime solution for a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The rough surface of CFRP showed superior bond strength when compared to the smooth surface of CFRP [4]. The geometry, in terms of length and width, of CFRP is a major factor that shapes the bond strength [5]. The durability of CFRP materials in different environments is one of the primary issues that has limited the development of these materials in the application of some infrastructure [6].…”
Section: Introductionmentioning
confidence: 99%
“…The rough surface of CFRP showed superior bond strength when compared to the smooth surface of CFRP [4]. The geometry, in terms of length and width, of CFRP is a major factor that shapes the bond strength [5]. The durability of CFRP materials in different environments is one of the primary issues that has limited the development of these materials in the application of some infrastructure [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the study of bond behavior between CFRP sheets and corrosion-cracked concrete surface is limited. Haddad et al [ 20 , 21 , 22 ] conducted experiments on this gap and found that corrosion-induced cracking caused a significant reduction in bond strength, slippage at ultimate stress and bond stiffness. However, the design scheme of the specimens in their study did not accurately simulate the actual CFRP strengthening scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Roughness parameter was introduced and proposed the optimum roughness for the best interface behavior. Haddad (2019) conducted an experimental study on the bonding behavior between CFRP and cracked concrete, 15 pull-off specimens were tested and its test results were analyzed. It indicated that the bonding behavior between CFRP and cracked concrete mainly affected by the concrete status, CFRP plate shape and anchorage measure.…”
Section: Introductionmentioning
confidence: 99%